A Hadith-Based Character Education Strategy for Children to Face the Challenges of Digital Disruption - Irfan Khilmi Faliza; Mahmut Oğuzhan; Erwin Tubagus; Arif Hidayat Syah; Ernie Marlinda Tamara (Yayasan Albahriah Jamiah Indonesia, 2026)
Digital disruption, characterized by the widespread adoption of information technology and social media, has led to the degradation of moral values, weakened self-control, and distorted social interactions among children and adolescents, as reflected in various global reports on the risks of digital behavior among children and adolescents. These problems demonstrate the limitations of contemporary character education approaches that tend to be normative-instrumental and have not been integrated with operational prophetic values. This study aims to develop a strategic conceptual framework for hadith-based children’s character education that is adaptive to the challenges of digital disruption. The study uses a systematic literature review design based on qualitative content analysis, tracing hadith from authoritative books (kutub al-Sittah) selected according to authenticity criteria (ṣaḥīḥ and ḥasan), then analyzing them through thematic analysis stages that include categorization, coding, and contextual interpretation. The results of the study indicate that the hadiths for children’s character education are structured in four interconnected strategic dimensions: first, spiritual values that build transcendental awareness as the basis for digital responsibility; second, moral-ethical values that emphasize honesty, trustworthiness, and etiquette in content production and consumption; third, social values that strengthen empathy, ethical communication, and concern in virtual interactions; and fourth, the values of discipline and self-control that function as internal regulatory mechanisms against distraction, impulsivity, and technology overuse. These four dimensions are formulated within an operational and contextually integrated conceptual framework for children’s character education in the digital era. Thus, hadith-based character education offers a holistic and adaptive prophetic model as a strategic solution in facing digital disruption.